Want this question answered?
Be notified when an answer is posted
associative? single replacement
Without an equality sign the information given can't be considered as an equation
The probability of ac and bc is 1/5.
There is no distributive property of addition over multiplication. The equation works if a + (b * c) = (a + b)*(a + c) = a2 + ab +ac +bc => a + bc = a2 + ab +ac +bc ie a = a2 + ab + ac = a*(a+b+c) and that, in turn requires that a = 0 or a+b+c = 1 If a, b and c are fractions than the second condition requires the fractions to sum to 1 - not be equal to 1.
(a + b)/(a - b) = (c + d)/(c - d) cross multiply(a + b)(c - d) = (a - b)(c + d)ac - ad + bc - bd = ac + ad - bc - bd-ad + bc = -bc + ad-ad - ad = - bc - bc-2ad = -2bcad = bc that is the product of the means equals the product of the extremesa/b = b/c
A+BC+AC+B=A+BC+AC+B unless any of these variables has an assigned value.
associative? single replacement
associative? single replacement
Without an equality sign the information given can't be considered as an equation
A general equation showing one nonmetal replacing another nonmetal in a compound is represented by the following formula: A + BC -> AC + B. Here, element A (a nonmetal) displaces element B in compound BC to form a new compound AC.
A single replacement reaction equation consists of a reactant compound and a new product compound formed by the replacement of an element in the reactant with another element. The general form is: A + BC -> AC + B, where A and B are elements, and BC is a compound.
The probability of ac and bc is 1/5.
There is no distributive property of addition over multiplication. The equation works if a + (b * c) = (a + b)*(a + c) = a2 + ab +ac +bc => a + bc = a2 + ab +ac +bc ie a = a2 + ab + ac = a*(a+b+c) and that, in turn requires that a = 0 or a+b+c = 1 If a, b and c are fractions than the second condition requires the fractions to sum to 1 - not be equal to 1.
a+bc --> ac+b
.Ab + c cb + a
(a + b)/(a - b) = (c + d)/(c - d) cross multiply(a + b)(c - d) = (a - b)(c + d)ac - ad + bc - bd = ac + ad - bc - bd-ad + bc = -bc + ad-ad - ad = - bc - bc-2ad = -2bcad = bc that is the product of the means equals the product of the extremesa/b = b/c
A+bc---> b+ac